IMPACT OF DIABETIC FOOT EXERCISE ON ANKLE-BRACHIAL INDEX IN PATIENTS WITH DIABETES - Rudini, Dini; Anita Sari, Lisa; Ekawaty, Fadliyana; Sulistiawan, Andika (International Archives of Medical Sciences and Public Health, 2026)
This study examined the effect of structured diabetic foot exercise on Ankle-Brachial Index (ABI) values among patients with type 2 diabetes mellitus (T2DM) at Simpang Kawat Public Health Center, Indonesia. A quasi-experimental one-group pretest–posttest design was applied in volving 35 participants selected through purposive sampling. Participants completed two supervised diabetic foot exercise sessions over one week. ABI measurements were performed before and after the intervention using a calibrated vascular Doppler under standardized conditions. Data were analyzed using paired-sample t-tests, and effect sizes were calculated using Cohen’s d. The results showed a significant increase in mean ABI values from 0.89 ± 0.06 to 0.94 ± 0.05 after the intervention (p < 0.001). Large effect sizes were identified in both the right and left lower extremities (d = 1.39 and d = 1.28), indicating meaningful clinical improvement in peripheral circulation. These findings suggest that structured diabetic foot exercise may support circulation focused diabetes self-management and has potential to be implemented as a practical non-pharmacological intervention in primary-care settings. However, the absence of a control group and short intervention period remain important study limitations.